Analysis and Development of A Self-Dimming Module for Road Traffic Signals - Nur Diyana; Subramaniam, Siva Kumar; Esro, Mazran; Panessai, Ismail Yusuf (International Journal of Recent Technology and Applied Science (IJORTAS), 2023)
Nowadays, we often see more and more of the various types of lights in urban areas, especially in road areas, either regarding the use of traffic lights or streetlights that serve as guides and signals to maintain road safety. Typically, the lamps use LED-based lamps as they can increase the rate of high savings. This LED conceptual light helps reduce energy wastage by using less power and reducing the consumption of heat and is suitable for day-to-day operation. The addition of ordinary LEDs to self-dimming systems based on the intensity of light around is more likely to increase the savings rate and is more environment-friendly. The scope of this research includes analytics data from the use of standard traffic lights and LED signal lights that are self-concept in dimmer systems. This research uses the IoT concept that is applied to the traffic system and uses solar energy which is indeed renewable natural energy and can affect the green earth concept to the traffic control system on the road.